Evaluation of comparative effectiveness research: a practical tool. (21st February 2018) - Schaumberg, Debra A; McDonald, Laura; Shah, Surbhi; Stokes, Michael; Nordstrom, Beth L; Ramagopalan, Sreeram V
Comparative effectiveness research (CER) guidelines have been developed to direct the field toward the most rigorous study methodologies. A challenge, however, is how to ensure the best evidence is generated, and how to translate methodologically complex or nuanced CER findings into usable medical evidence. To reach that goal, it is important that both researchers and end users of CER output become knowledgeable about the elements that impact the quality and interpretability of CER. This paper distilled guidance on CER into a practical tool to assist both researchers and nonexperts with the critical review and interpretation of CER, with a focus on issues particularly relevant to CER in oncology.